Uji Aktivitas Antibakteri Ekstrak Etanol Daun Ungu (Graptophyllum pictum (L) Griff) terhadap Pertumbuhan Streptococcus sanguinis - Syahrani, Nafila; Kurniawati, Atik; Prihanti, Ayu Mahartini; Sulistyani, Erna; Lestari, Pujiana Endah (UPT Percetakan dan Penerbitan Universitas Jember, 2024)
Streptococcus sanguinis has strong adhesion with salivary pellicles which causes other oral bacteria to attach more and has contribution in causing caries and periodontal disease. S. sanguinis mediated the adhesion of S. mutans to dental pellicle receptors so inhibiting the interaction between S. sanguinis and S. mutans would prevent the risk of dental caries. Purple leaf (Graptophyllum pictum) is one of the medicinal plants or natural ingredients that are useful as antibacterials. The purpose of this study was to examine antibacterial activity of purple leaf extract against S. sanguinis. This experimental laboratory study with a pre-posttest control group design was conducted by dilution method on treatment groups, purple leaf extract with concentrations of 25%, 12.5%, 6.25% and 3.12%. Visual and spectrophotometer examination was observed before and after incubation.The result showed that purple leaf extract with concentrations of 6.25% and 3.12% and control + groups had not turbidity and decreased absorbance value. Furthermore, the One Way Anova parametric statistical test and also Post-Hoc Least Significant Difference showed that there were significant differences between the study groups. The purple leaf extract (Graptophyllum pictum L. Griff) had antibacterial activity against S. sanguinis. The antibacterial test for extracts that are dark in color can be continued using the TVC (Total Viable Count) method to provide a quantitative estimate of the concentration of bacterial cells in the sample in units of CFU/ml.